Stages of the creation of the fetus and the stages of its development in Sharia and medicine (Journal of Misan Researches, 2023)
Knowing and examining the stages of the fetus and the stages of its development and upbringing have great benefits in diagnosing the periods and durations of those stages and life stages and explaining their characteristics, in order to preserve it, provide protection for it, persevere in its care, and take care of the mother who carries him and her sensitive conditions that she goes through, especially at the time of pregnancy. May God not forgive in the event of its abortion and abortion, the legislator can determine and rank the material and moral value according to that and according to the phase and stage that he is finished with, as is the current and practiced by some specialists in jurisprudence and law. To make it in his way, and to spread its benefit, he is the guardian of grace and generosity.